Colorful and semi durable antioxidant finish of woolen yarn with tannin rich extract of Acacia nilotica natural dye. (April 2017) - Rather, Luqman Jameel; Akhter, Sabiyah; Padder, Rayees Ahmad; Hassan, Qazi Parvaiz; Hussain, Mohammad; Khan, Mohd Ali; Mohammad, Faqeer
Abstract: Evaluations of coloring potential, antioxidant activity, and toxicological studies of Acacia nilotica bark extract onto woolen yarn were performed with the aim of developing bioactive fibers for use in medical textile sector. In the present study, we present dyeing potential, colorimetric characteristics (CIEL*a*b* and K/S), and fastness properties of Acacia nilotica dyed woolen yarn with the optimization of affecting conditions through conventional one-factor-at-a-time (OFT) optimization technique using reflectance spectroscopic analysis. Four most important operating parameters namely pH, time, temperature, and dye concentration were optimized in terms of color strength (K/S) values for producing textile materials of acceptable colorimetric and fastness characteristics. Use of different metal salts (alum, ferrous sulfate, and stannous chloride) has improved color characteristics and fastness properties of dyed textile materials. Antioxidant potential of hydroalcholic bark extract of Acacia nilotica was evaluated in terms of reducing power and inhibition of peroxidation by 2, 2′-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging activity and subsequently dyed woolen yarn in terms of inhibition of peroxidation by DPPH assay and compared with that of the ascorbic acid used as positive control. Mordanting reduced the antioxidant activity of dyed woolen yarn as compared to unmordanted samples. Wash durability results proved successful antioxidant finishing of woolen yarn dyed with Acacia nilotica bark extract. Reduction in antioxidant activity on successive washing cycles follows 1st order rate equation. Haemolytic activity on rat erythrocytes were studied to exclude possibility of any associated cytotoxicity. The observed antioxidant characteristics and negligible cytoxicity of Acacia nilotica indicate that the dye might be a promising antioxidant finishing agent for developing bioactive textile materials and clothing in near future. Highlights: First time application of Acacia nilotica as an ecofriendly antioxidant finishing agent. Reflectance spectroscopic analysis was used to optimize the dye affecting conditions. Dark brown to yellowish shades were obtained with acceptable colorimetric properties. Acacia nilotic a finished woolen yarn showed excellent DPPH scavenging activity. Decrease in antioxidant activity as a function of washing cycles followed 1st order kinetic equation.